Development and use of information technology for evaluating an operator’s visual profile functional state - Сайківська, Лілія Федорівна (Technology audit and production reserves, 2015)
The article presents the information technology of functional assessment of visual profile of the operator, which allows to record the performance with the help of hardware and software, to carry out the selection of informative indicators based on the minimization of their connectedness and predict changes in this state in the process of visual work with different kinds of visual load. It is shown the possibility of using the correlation method and calculated with the help of the multicollinearity index to determine the optimal set of indicators of the functional state of the subjects and research degree of tension and mobilization of the body in the process of visual work Information processing algorithm about the functional status of the operator of the visual profile, that proposed in the article, can be used not only to assess the current functional state and predict changes in the condition of the original in the performance of different types of visual problems, but also to forecast the state of the operator for a wide range of tasks.